MADURA DEVELOPMENT PLAN AS A DESTINATION SYARIAH INDONESIA TOURISM - Sutikno Sutikno; Ahmad Kamil; Mohd Shukri Hanapi (Univeristas Islam Bandung, 2020)
This study aims analyze the potential of attractions in Madura to become sharia tourism destinations. Next will measure the level of community readiness and development strategies for Islamic tourism in Madura. To analyze the potential of sharia tourism objects, they use observational analysis and public perceptions about the suitability of tourism objects with sharia tourism. As for the analysis of the development of Islamic tourism on the island of Madura using the Analytical Hierarchy Process method. The results showed that, Madura has the potential to become a sharia tourist destination, because has a potential tourist attraction to be developed into an Islamic tourist attraction. Second , the Madurese people already have an understanding of sharia tourism, this will be a big capital for Madura to become sharia tourism destinations in Indonesia. Citizen Branding Strategy can be a top priority in efforts to develop Islamic tourism on the island of Madura.